LEGAL POLICY ON EXHIBITIONISM THROUGH VIDEO CALL-BASED SOCIAL MEDIA REVIEWED FROM THE INFORMATION AND ELECTRONIC TRANSACTIONS (IET) LAW - Suarsika, I Komang; Wiratny, Ni Ketut; Sihotang, Erikson (jfpublisher, 2024)
The advancement of information technology has significantly impacted society, transforming conventional crimes into cybercrimes using computers and the internet. One such example is exhibitionism via video call-based social media. This act is not yet specifically addressed in the Information and Electronic Transactions (IET) Law. Applying Article 27 Paragraph (1) of the IET Law, which deals with indecent acts, does not cover this scenario as it lacks the